HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEKAMBUHAN HIPERTENSI PADA LANSIA DI DESA GONDORUSO KECAMATAN PASIRIAN KABUPATEN LUMAJANG - Eka Suryaningtyas; ISHANA BALAPUTRA; ALI MASHUDA (MEDICAL JURNAL OF AL-QODIRI, 2019)
Latar belakang: Health problems and economic is the main problems the elderly, because relating to a setback physical man occurring in natural and related to meeting the needs of life.Throughout the world today, the number of elderly it is estimated that more than 629 million people, and in the end of 2025 projected the number of elderly will reach 1.2 billion.Research objectives know relations family encouragement on the level of a recurrence hypertension in elderly. Metode: The kind of research use is deskritip correlative using design cross sectional. The number of respondents is 40 respondents meet the criteria inclusion by using the method proposive sampling Hasil: Having undergone a data using spearment rank got that sig value. By 0,000 & it; 0,05 because the value of sig (2-tailed) of 0,000 smaller than 0,05 so it can be concluded that the significant (p) the relationship between a family with a recurrence hypertension on elderly. Kesimpulan: It is expected to the more vulnerable to elderly who live with them that elderly experienced diseases such as hypertension.Support will be koping strategy that is essential for by the while he was stress.The existence of support adekuat proved associated with declining mortalitas, easier convalescents, and among the old, cognitive function, physical and emotional health.